Carving the Future: Career Aspirations of Senior Dental Students in Saudi Arabia - Nassani, Mohammad Z.; Alsalhani, Anas B.; Alasmari, Alwaleed A.; Alqahtani, Waleed S.; Rastam, Samer; Shamsy, Enass; Noushad, Mohammed; Sakka, Salah; Alali, Faisal M.; Tarakji, Bassel; Ali, Kamran; Al-Maweri, Sadeq A. (European Journal of Dentistry, 2025)
This study investigates the future career plans of senior dental students in Saudi Arabia and the factors influencing these plans.An online questionnaire-based survey, designed following STROBE guidelines, was conducted. Participants included final-year dental students and interns from dental institutions across Saudi Arabia. The survey collected demographic data, career preferences, and factors potentially impacting career choices.A total of 584 students from 12 dental schools participated. Most respondents (63.5%) reported receiving career guidance, with 87.5% expressing interest in postgraduate studies and 11.3% preferring to work as general dental practitioners. A significant proportion (63.2%) favored employment in the government sector, while 12.8% preferred the private sector. Endodontics was the most preferred specialty (15.4%), followed by orthodontics (13.2%), periodontics (12.5%), and prosthodontics (12%). Additionally, 28.4% planned to retire before the age of 50 years. Career plans were significantly associated with gender, grade point average (GPA), and receipt of career guidance (p < 0.05). Personal aspirations were the most influential factor in career decision-making, followed by the reputation of a postgraduate program and the demands of the national job market. Predictors of interest in postgraduate studies included a high GPA, graduation from a public university, and receiving career guidance from dental schools.Saudi dental students demonstrated diverse career aspirations, with a strong inclination toward postgraduate education and government sector employment. Given the importance of career guidance as a predictor of postgraduate interest, Saudi educational, health, and labor authorities should consider aligning students' career goals with the evolving demands of the national job market.
Keywords: career choice; career guidance; dental students; dentistry; Saudi Arabia